Підвищення ефективності виявлення БПЛА по акустичному випромінюванню - Шафроненко, Є. О. (ХНУРЕ, 2025)
Unmanned aerial vehicles (UAVs) have rapidly gained prominence in a wide array of applications, ranging from military operations such as reconnaissance, surveillance, and target acquisition, to civilian uses such as cargo delivery, monitoring, and environmental research. Their ability to operate autonomously and maneuver with precision at relatively low altitudes provides tactical advantages, making them valuable assets across diverse fields. However, these very characteristics of high maneuverability, low flight altitude, and compact size – pose significant challenges for detection systems, which are designed to identify, track, and neutralize aerial threats.
Keywords: акустичне випромінювання; виявлення БПЛА